A breakthrough research to understand Brazilian backwoods culture - Campos, Judas Tadeu de (Estudos Avançados, 2012)
The anthropologist Emilio Willems produced, in the middle of the 1940 decade, the first Brazilian community study. He did the research in the municipality of Cunha, located in a highland country, between the Quebra-Cangalha and Mar mountains, in the Paraiba Valley. But that study had another attribute: it is considered a precursor academic inquiry to treat respectfully and to give a significant contribution for the understanding of the caipira culture, that is, the way of life of the early dwellers in the rural area in the State of Sao Paulo. This text search demonstrate how that work was realized, the receptivity which it had in the academicals ambiences and his repercussions in others sociological researches.